Analysis of the gene encoding the RNA subunit of ribonuclease P from cyanobacteria. - Vioque, A (1992)
The genes encoding the RNA subunit of ribonuclease P from the unicellular cyanobacterium Synechocystis sp. PCC 6803, and from the heterocyst-forming strains Anabaena sp. PCC 7120 and Calothrix sp. PCC 7601 were cloned using the homologous gene from Anacystis nidulans (Synechococcus sp. PCC 6301) as a probe. The genes and the flanking regions were sequenced. The genes from Anabaena and Calothrix are flanked at their 3'-ends by short tandemly repeated repetitive (STRR) sequences. In addition, two other sets of STRR sequences were detected within the transcribed regions of the Anabaena and Calothrix genes, increasing the length of a variable secondary structure element present in many RNA subunits of ribonuclease P from eubacteria. The ends of the mature RNAs were determined by primer extension and RNase protection. The predicted secondary structure of the three RNAs studied is similar to that of Anacystis and although some idiosyncrasies are observed, fits well with the eubacterial consensus.